Getting Started - Barney G. Glaser (Grounded Theory Review: An International Journal)
It may sometimes be said that one of the most difficult parts of doing research is to get started. The making of choices and commitments to a research problem seem less secured and structured when doing descriptive research in quantitative or qualitative research. This occurs because the research problem is chosen beforehand and therefore forces the data, thus the yield may be small or nothing since the problem in fact may not be relevant. A “thought up” problem may sound juicy, but the preconception leads nowhere.